Associations of sex hormone ratios with metabolic syndrome and inflammation in US adult men and women - Dubey, Pallavi; Singh, Vishwajeet; Venishetty, Nikit; Trivedi, Meesha; Reddy, Sireesha Y.; Lakshmanaswamy, Rajkumar; Dwivedi, Alok Kumar (Frontiers in Endocrinology, 2024)
Background: Sex hormones play a critical role in sex differences and cardiovascular disease risk associated with metabolic syndrome (MS) and inflammation. However, the associations of sex hormone ratios with metabolic and inflammatory markers are unclear according to sex and age differences. We evaluated the associations of sex hormone ratios with MS and inflammation among males and females. Methods: A retrospective cross-sectional study was conducted by including all adults from the National Health and Nutrition Examination Survey cycles 2013-2016 and excluding any pregnant women, heart disease, diabetes, and those currently taking insulin. MS was defined using the National Cholesterol Education Program criteria and a high-sensitivity C-reactive protein (CRP) level>3 mg/L was defined as a high CRP. Measures of MS components and CRP concentrations were also analyzed. The primary exposures were testosterone to estradiol (excess androgen index), testosterone to sex hormone-binding globulin (free androgen index), and estradiol to sex hormone-binding globulin (free estradiol index). The adjusted associations were summarized with a relative risk (RR) and 95% confidence interval (CI). Results: This study included 9167 subjects with 4360 males and 4807 females. Increases in free estradiol index were positively associated with MS (RR=1.48; 95%CI: 1.39, 1.58; RR=1.31; 95%CI: 1.22, 1.40) and high CRP (RR=1.49; 95%CI: 1.25, 1.77; RR=1.26; 95%CI: 1.06, 1.50) in men with age<50 years and age≥50 years, respectively. Similarly, higher free estradiol index was also robustly associated with increased prevalence of MS (RR=1.22; 95%CI: 1.15, 1.28) and high CRP (RR=1.68; 95%CI: 1.48, 1.90) in women with age ≥50 years. Among women with age<50 years, a higher free androgen index was associated with MS (RR=1.34; 95%CI: 1.25, 1.42) and high CRP (RR=1.13; 95%CI: 1.02, 1.25). These associations were unchanged even after adjusting for all sex hormones. Conclusions: Free estradiol index was consistently and positively associated with MS and high CRP in males of all ages and older females. Free androgen index was positively associated with MS and high CRP in females with age<50 years.